Chemokines involved in the early inflammatory response and in pro-tumoral activity in asbestos-exposed workers from an Italian coastal area with territorial clusters of pleural malignant mesothelioma. (April 2016) - Comar, M.; Zanotta, N.; Zanconati, F.; Cortale, M.; Bonotti, A.; Cristaudo, A.; Bovenzi, M.
Highlights: Specific growth factors were observed in sera of asbestos exposed workers. The chemokines IP-10 and RANTES were associated with the severity of diseases. RANTES showed the highest serum level. RANTES showed a significant relationship between sera and pleural effusions. Mesothelioma biopsies showed detectable levels for RANTES, VEGF, and IP-10. Abstract: Objectives: Immune mediators are likely to be relevant for the biological response to asbestos exposure. The aim of this study was to investigate the association between immune mediators involved in inflammation, cell survival and angiogenesis, and asbestos-related diseases in workers from a coastal area of North-East Italy with a high incidence of pleural malignant mesothelioma (PMM). Materials and methods: A selected custom set of 12 soluble mediators was evaluated with a Luminex platform in sera, pleural fluid and mesothelioma biopsies from 123 asbestos-exposed workers (38 free from pleural-pulmonary disorders, 46 with non-malignant asbestos diseases, 39 with PMM) and in sera from 33 healthy controls from the same territorial area. Results: Increased immune mediator concentrations were observed in the sera of the asbestos-exposed workers compared to controls for human fibroblast growth factor (FGF-b), vascular endothelial growth factor (VEGF), CCL5 (RANTES), CXCL10 (IP-10), CLEC11A (SCGF-b), CCL27 (CTACK), CCL11 (EOTAXIN), IL-5 and IL-6 ( p < 0.001). The chemokines IP-10 and RANTES were associated with the severity of asbestos-related diseases. In the workers with PMM, the immune proteins secreted by mesothelioma biopsies showed detectable levels of RANTES, VEGF, and IP-10. In the same workers with PMM, a significant relationship between serum and pleural fluid concentrations was found for RANTES alone. Conclusions: Occupational exposure to asbestos seems to drive the production of specific growth factors dually involved in the early inflammatory response and in pro-tumoral activity before clinical evidence of related disorders, suggesting that their over-expression may precede the onset of asbestos-related diseases. These findings suggest that some chemokines may have a prognostic role in the progression of asbestos-related diseases and could be used for the health surveillance of either workers with an occupational history of asbestos exposure or patients affected by non-malignant asbestos-related diseases.